Evaluation of the implementation of workshop and laboratory management on vocational high school - Fuadillah Pangestu; Sukardi Sukardi (Jurnal Pendidikan Vokasi, 2019)
This research aims to reveal: the development of workshop and laboratory management implementation, also the suitability of facilities and infrastructure on Vocational High School in Banggai District, which refers to the indicator of good workshop and laboratory, according to the Directorate of Vocational Education. This research is evaluation research, which employs a goal free evaluation model and descriptive quantitative approach. The research sample involved in this study was 187 teachers and students. The data analysis technique used in this research was the average score and skewness. The result of this research shows that: (1) The workshop development is appropriate enough and good, yet it still needs further improvement with students to score at 81.19 and -0.229 also the teachers at 197.78 and -0.433. (2) The laboratory development is appropriate enough, and it still needs further improvement with students to score at 96.64 and 0.393, also the teachers at 209.03 and 0.36. (3) The suitability of the workshop's facilities and infrastructure is appropriate enough, and it still needs further improvement with the score at 250.205 and 0.549, and also the laboratory is appropriate enough and good, yet it still needs further improvement with the score at 252.80 and -1.694.